2021
DOI: 10.1126/science.abd2893
|View full text |Cite
|
Sign up to set email alerts
|

Thymic stromal lymphopoietin induces adipose loss through sebum hypersecretion

Abstract: Emerging studies indicate that the immune system can regulate systemic metabolism. Here, we show that thymic stromal lymphopoietin (TSLP) stimulates T cells to induce selective white adipose loss, which protects against obesity, improves glucose metabolism, and mitigates nonalcoholic steatohepatitis. Unexpectedly, adipose loss was not caused by alterations in food intake, absorption, or energy expenditure. Rather, it was induced by the excessive loss of lipids through the skin as sebum. TSLP and T cells regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 69 publications
0
33
0
1
Order By: Relevance
“…In the murine model, it has been found that TSLP overexpression caused WAT loss by inducing skin T-cell migration and increasing sebum hypersecretion. WAT loss was independent of ILCs2, eosinophils, and T reg cells [23].…”
Section: Discussion/conclusionmentioning
confidence: 94%
“…In the murine model, it has been found that TSLP overexpression caused WAT loss by inducing skin T-cell migration and increasing sebum hypersecretion. WAT loss was independent of ILCs2, eosinophils, and T reg cells [23].…”
Section: Discussion/conclusionmentioning
confidence: 94%
“…Our immunostaining suggests that keratinocytes are not the sole source of TSLP during homeostatic hair cycle and wounding healing and that additional immune and non-immune cells in the dermis contribute to local TSLP production. Emerging evidence has delineated TSLP functions in airway epithelial cell migration ( Kabata et al., 2020 ), T Reg expansion ( Leichner et al., 2017 ), innate lymphoid cell activation ( Kim et al., 2013 ), and sebaceous gland activity ( Choa et al., 2021 ). We expect that TSLP exhibits pleiotropic activity beyond the known functions in the skin and other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous TSLP controls the steady-state level of sebum secretion and sebum-associated antimicrobial peptide expression through the activation of T cells in murine skin. TSLP overexpression results in loss of white adipose tissue in conjunction with sebum hypersecretion ( 18 ). TSLP helps to maintain skin-resident RORγt + ILCs within hair follicles, and, by the virtue of their location, ILCs negatively regulate surrounding sebaceous gland size and lipid content to regulate commensal bacteria equilibrium and fine-tune the skin barrier surface in mice ( 198 ).…”
Section: Beyond the Role Of Type 2 Cytokines As Alarmins In Skin Healthmentioning
confidence: 99%
“…A diverse range of immune cell types, including several T cell subsets, macrophages, dendritic cells (DCs), innate lymphoid cells (ILCs), and mast cells, is localized around vasculature and extracellular matrix proteins in the dermis ( 14 16 ). This complex network of dermal immune cells helps in many aspects of host physiology, including protection against pathogens, wound healing ( 17 ), sebum production ( 18 ), and hair follicle homeostasis ( 19 ).…”
Section: Introductionmentioning
confidence: 99%